Conciliation Versus Mediation of Complaints Against Police: Lessons from the Queensland Experience - M. Riley; T. Prenzler (Russian Journal of Economics and Law, 2020)
Objective: to analyze the dispute resolution practices for dealing with citizen-initiated complaints against police in Queensland, Australia.Methods: dialectical approach to cognition of social phenomena, allowing to analyze them in historical development and functioning in the context of the totality of objective and subjective factors, which predetermined the choice of the following research methods: formal-logical, comparative-legal, and sociological. Results: since the 1990s, alternative dispute resolution practices for dealing with citizen-initiated complaints against police, such as conciliation, have progressively been trialed and implemented in police services across Australia. The Queensland Police Service was one of the most proactive services in trialing independently facilitated complaints mediation programs - in collaboration with its oversight agency. However, despite repeated positive outcomes, the Service refrained from actively using mediation, preferring instead to use management dominated informal resolution (conciliation). This process, characterized by police investigating police, continues to limit complainant participation by denying them the opportunity to meet face- to-face with the subject officer. Yet the literature cites mediation, especially practices based on restorative principles as beneficial because it brings disputing parties together in dialogue that is educative for both parties, reparatory, and better satisfies complainants’ aspirations for an inclusive and neutral complaints system, while data from mediated complaints can also be used to inform police conduct improvement strategies. Complaints mediation is available upon request within the Queensland Police Service, however, it is not widely promoted, and is internally facilitated.Scientific novelty: this article presents an historical account of the application of mediation and conciliation to the Queensland Police Service complaints system. The authors answer the question why conciliation has become the default approach and mediation continues to be largely ignored. This is done through a qualitative analysis of publicly available documents and semi-structured interviews with key stakeholders. The findings reveal that the 1992 Mediation Pilot was very successful. However, the Queensland Police Service adopted conciliation because it was cheaper and, they claim, better aligned with managing behavioral improvements. Three decades on, there has been little evidence of this, while the literature clearly shows that mediation should be a key component of any police complaints and discipline system. The findings reveal that the 1992 Mediation Pilot was very successful. However, the Queensland Police Service adopted conciliation because it was cheaper and, they claim, better aligned with managing behavioral improvements. Three decades on, there has been little evidence of this, while the literature clearly shows that mediation should be a key component of any police complaints and discipline system.Practical significance: the main provisions and conclusions of the article can be used in scientific, pedagogical and law enforcement activities when considering issues related to the citizens’ claims on the actions of law enforcers.